Experimental Tests of the Vector II Slab in Field Conditions, Slab and Strip Model - Zając, Jakub; Drobiec, Łukasz; Jasiński, Radosław; Wieczorek, Mirosław; Kisiołek, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Vector II slab was tested on a natural scale (a slab with a dimension of 6.30 x 6.30 m) and a strip 6.30 m long and 1.20 m wide. The Vector II slab is built by precast panel 60 cm wide, 4 cm thick and 14-20 cm thick concrete overtopping on the construction site. The main purpose of the slab tests on a natural scale was to observe the "faulting" effect and temporary deflections. During the tests, the displacements in the area of the panel joints in the middle of the slab span were recorded.
Keywords: crack pattern; flexural analysis; interface; precast; slab; short-term load; pęknięcie; zginanie; prefabrykaty; płyty; obciążenie krótkotrwałe